Evoking the four dimensions of student knowledge in ecosystem: effectiveness of real object, web, and blended learning - Anwar Musyaddad; Slamet Suyanto (Biosfer: Jurnal Pendidikan Biologi, 2019)
This research aims to: identify whether there is a significant difference in influence between learning media based on real object, web, and blended learning on student knowledge dimension, which covers factual, conceptual, procedural, and metacognitive knowledge on ecosystem material. It was a quasi-experiment with a pretest-posttest comparison group design. The population in this study was all students of class X MIA in SMA N 1 Bantul and SMA N 2 Bantul in semester 2 of the 2018/2019 academic year. The sample in this study used three experimental classes that were randomly selected using cluster random sampling techniques. The data were collected using tests of factual, conceptual, procedural, and metacognitive knowledge and student's metacognitive questionnaire. These data were then analyzed using the Multivariate Analysis of Variants test. The results demonstrate that: (1) learning media based on real object, web and blended learning affect the student’s factual, conceptual, procedural and metacognitive knowledge, (2) there is a significant difference in effectiveness between learning media based on real object, web and blended learning on students' factual, conceptual and metacognitive knowledge, (3) there is no significant difference in effectiveness between learning media based on real object, web and blended learning on students' procedural knowledge. Based on this, it can be recommended that biology learning media based on real object and blended learning can be applied by the teacher to improve students' factual, conceptual, and metacognitive knowledge.